Molecular classification of head and neck squamous cell carcinoma based on hypoxia-related genes and clinical significance of STC2 - ZHU Jianing, WANG Tiantian, ZHANG Rui, SONG Hongquan (口腔疾病防治)
Objective To construct a molecular classification system for head and neck squamous cell carcinoma (HNSCC) utilizing hypoxia-related gene (HAG) expression profiles, and to comprehensively examine the clinicopathological significance and biological functions of the hypoxia gene stanniocalcin 2 (STC2) in HNSCC. Methods Transcriptomic data and clinical information of 546 HNSCC samples were obtained from The Cancer Genome Atlas (TCGA) database, and based on the expression profiles of 200 HRGs, HNSCC was classified subclasses using non-negative matrix factorization (NMF). HNSCC was classified into three subclasses (C1, C2, and C3), and the molecular characteristics and prognostic differences of the subclasses were assessed by comparing the tumor mutation load, functional enrichment analysis, drug sensitivity, and clinical features among the subclasses. LASSO-Cox regression was used to screen prognosis-related genes and construct prognostic models. Using oral squamous cell carcinoma (OSCC)-related data in the TCGA database, we analyzed the expression differences of STC2 in OSCC and control samples, and detected the mRNA and protein expression of STC2 in oral squamous carcinoma samples using qRT-PCR and immunohistochemistry. We knocked down STC2 in CAL-27 cells and verified the knockdown efficiency by qRT-PCR and Western blot. CCK-8 assay and cell scratch assay were used to assess the effect of STC2 on cell proliferation and migration ability. Results Based on HRGs expression profiles, HNSCC was categorized into three subclasses (C1, C2, and C3). Subclass C1 had moderate hypoxic activity and good prognosis; subclass C2 had the highest hypoxic activity, poor prognosis, and poor sensitivity to CTLA-4 inhibitors (P<0.05); subclass C3 had the lowest hypoxic activity and moderate prognosis, and STC2 belonged to subclass C3. The frequency of cyclin-dependent kinase inhibitor 2A (CDKN2A), phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), and tumor protein p53 (TP 53) mutations was higher in HNSCC. C1 genomic gain and deletion burden were significantly higher than C3 subclass (P<0.05) and C2 genomic gain than C3 subclass (P<0.05). The C2 subclass was significantly enriched in hypoxia-associated pathways, such as glycine metabolism and base excision repair (P<0.05). The C1, C2, and C3 subclasses were significantly positively correlated in terms of sex (male) (Cramer’s V=0.15), radiation exposure (Cramer’s V=0.12), medication (Cramer’s V=0.18), and pathological grading (G1/G2) (Cramer’s V=0.25) (P<0.05). Nine prognosis-related genes were screened by LASSO-Cox regression, among which high expression of STC2 was positively correlated with poorer overall survival (OS) in HNSCC patients (P<0.01). Bioinformatics analysis showed that STC2 mRNA expression was higher in OSCC than in normal controls (P<0.05). qRT-PCR and immunohistochemistry confirmed that both mRNA and protein expression of STC2 were significantly upregulated in OSCC tissues and cells (P<0.01). In vitro experiments showed that STC2 expression was knocked down to approximately 80% in CAL-27 cells (P<0.001), and the STC2 knockdown group had a reduced value-added rate (P<0.001) and a reduced percentage of scratch closure (P<0.05) compared with the control group. Conclusion We successfully constructed a molecular typing system for HNSCC based on the expression profiles of HRGs and categorized HNSCC into three subclasses with significant prognostic differences, among which the C2 subclass had the highest hypoxic activity and the poorest prognosis. STC2 was highly expressed in HNSCC and suggested a poor prognosis, demonstrating that it may be a potential target for HNSCC treatment.